Efficacy of transbronchial biopsy and frequency of pneumothorax in lung transplant recipients: single center experience - Ertan Sarıbaş; Ayse Nigar Halis; Sevinç Çıtak; Gonca Gecmen; Ahmet Murat Kazan; Musatafa Vayvada; Murat Ersin Cardak; Ahmet Erdal Taşçı (BMC Pulmonary Medicine)
Abstract Objective Bronchoscopy plays a critical role in the diagnosis and management of lung transplant recipients. We retrospectively evaluated the safety, complications, and efficacy of transbronchial biopsy (TBB) in detecting and grading early rejection. Materials and methods We retrospectively assessed the complications associated with TBB and the adequacy of pathological diagnoses in patients who underwent lung transplantation at Koşuyolu Yüksek İhtisas Training and Research Hospital from December 1, 2016, to April 30, 2023. Results In this study, we retrospectively analyzed 290 TBB procedures performed on 59 out of 94 lung transplant recipients. Of the study cohort, 72.9% (n = 43) were male, with a median age of 44.3 years. The proficiency of TBB pathology was found to be 90.7% (n = 263) for acute rejection (AR), 46.5% (n = 135) for airway inflammation, 50% (n = 145) for chronic lung allograft dysfunction (CLAD) with bronchiolitis obliterans (BO), and 89.6% (n = 260) for chronic vascular rejection. Acute rejection (AR) was detected in 23.4% (n = 68). Pneumothorax was observed in 2.07% (n = 6) of the cases. A chest tube was inserted in four patients to manage pneumothorax, while two patients received only supplemental oxygen due to minimal pneumothorax. Conclusion TBB is considered a very safe procedure when basic precautions are followed. The rate of pneumothorax, a complication associated with TBB, is low. Despite advances in immunology and genetics, TBB remains the gold standard for detecting acute rejection (AR) following lung transplantation. Given its diagnostic value, we believe that the procedure should not be avoided due to the risks of complications.